Auricular Reconstruction: Surgical Innovations, Training Methods, and an Attempt for a Look Forward - Magritz, Ralph; Siegert, Ralf (Facial Plastic Surgery, 2014)
The construction of an auricle from autologous tissue is highly complex and demanding for a reconstructive surgeon. Depending on the characteristics of the underlying malformation, there are various surgical techniques available, which in specialized hands, promise regularly achievable attractive and stable results. To achieve this goal, a long-term training in super specialized centers is required. Training models available today, can partially systematize this training. The future of auricular reconstruction lies probably in the tissue engineering of organ complexes, including their nerve and vascular supply.
Keywords: auricular reconstruction; microtia; rib cartilage; autologous; training